Interenterprise Arrears in Post-Communist Economies - Rostowski, Jacek (IMF Working Papers; Working Paper ;, 1994)
The reasons for the growth of interenterprise debt are analyzed. It is suggested that it results mainly from the appearance of normal trade credit in a liberalized economy, and when a monetary squeeze is part of a stabilization attempt that is not credible. In the latter case, the result can be a sharp fall in output. Non-market and market solutions to this problem are analyzed, and the advantages of the latter over the former are stressed.